2006
DOI: 10.1093/eurpub/cki162
|View full text |Cite
|
Sign up to set email alerts
|

Peer education in HIV prevention: an evaluation in schools

Abstract: The peer education approach can influence the behaviour of young people regarding their personal protection from HIV infection. In order to test its effectiveness, peer education should be further evaluated as a health education method in HIV prevention in high schools, other youth settings and community interventions, where the aim is behavioural change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 11 publications
2
40
0
3
Order By: Relevance
“…We identified 1,123 titles from the search conducted in all databases. After screening the titles and abstracts, 84 studies were identified that met the inclusion criteria [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83] [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109] [110], [111], [112], [113], [114], [115], [116], [117], [118], [119], [120], [121], [122], [123], [124]; 51 studies were RCTs while 29 were quasi-experimental design and four were pre–post studies....…”
Section: Resultsmentioning
confidence: 99%
“…We identified 1,123 titles from the search conducted in all databases. After screening the titles and abstracts, 84 studies were identified that met the inclusion criteria [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83] [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108], [109] [110], [111], [112], [113], [114], [115], [116], [117], [118], [119], [120], [121], [122], [123], [124]; 51 studies were RCTs while 29 were quasi-experimental design and four were pre–post studies....…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that peer education has a significant impact in reducing risk behavior in young people. [16171819]…”
Section: Discussionmentioning
confidence: 99%
“…15 The present evaluation of the Sharing Stories program used a combination of arts-based and survey-based evaluation methods. The findings provide direction for other practitioners involved in sexual health education for multicultural groups where there is likely to be community support for arts-based interventions.…”
Section: Sharing Storiesmentioning
confidence: 99%